Nanoencapsulated Extracts from Leaves of Bauhinia forficata Link: In vitro Antioxidant, Toxicogenetic, and Hypoglycemic Activity Effects in Streptozotocin-induced Diabetic Mice - de Souza, Bárbara Verônica Cardoso; Ribeiro, Alessandra Braga; Oliveira, Rita de Cássia Meneses; Portela, Julianne Viana Freire; Cavalcante, Ana Amélia de Carvalho Melo; Barros, Esmeralda Maria Lustosa; Matos, Luís Felipe Lima; Alves, Tarsia Giabardo; Martins, Maria do Carmo de Carvalho e; Nunes, Lívio César Cunha (Archives of Pharmacy and Pharmaceutical Sciences, 2024)
In this study, we evaluated the assessed the hypoglycemiant, toxicogenetic and genotoxic effects of nanoencapsulate extracts of Bauhinia forficata Link. Phytochemical evaluations of extracts were carried out, as well as the evaluation using HPLC-MS and of antioxidant capacity in vitro. DM2 was induced in mice with streptozotocin and extracts were given orally for 28 days. That dried extract from infusion (ESIN) had a higher rate of bioactive compounds compared to the dried extract from decoction (ESDC), and higher antioxidant capacity. Glucose levels decreased from 77.26% to 57.79% and 45.15% after supplementation with ESIN (200 and 600 mg/kg/day) and ESDC (600 mg/kg/day), respectively, when compared to the diabetic group treated with metformin (600 mg/kg/day) (21.53%), with an improvement in the glycemic response e recovery of pancreatic β cells. Thus, our study has shown that these extracts exhibit hypoglycemiant activity, with a beneficial effect superior to metformin, as a result they could be considered as potential therapeutic agents for application in pharmaceutical formulations in the treatment of DM2.